2011
DOI: 10.1007/s12639-011-0059-y
|View full text |Cite
|
Sign up to set email alerts
|

SEM studies on blood cells of Plasmodium berghei infected Balb/c mice treated with artesunate and homeopathic medicine China

Abstract: The therapeutic efficacy of antimalarial drugs and their effect on various organs in the form of surface morphological deformations can be analyzed using scanning electron microscopy (SEM). Present study has been undertaken on Plasmodium berghei (NK-65), a lethal rodent malaria parasite, to monitor the morphological changes in blood cells induced by the treatment with combination of artesunate and homeopathic medicine . Combination therapy of artesunate (100 mg/kg) and China / was found to be highly effective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…During intraerythrocytic cycle after malaria infection, iRBCs underwent significant structural and biochemical modification. The modifications in the internal and membrane structures of iRBCs caused by invasion of malaria parasites were represented by morphological alterations of RBCs . Hb concentration in RBC cytoplasm decreases because Hb is digested by malaria parasites and is converted into hemozoin as a byproduct.…”
Section: Resultsmentioning
confidence: 99%
“…During intraerythrocytic cycle after malaria infection, iRBCs underwent significant structural and biochemical modification. The modifications in the internal and membrane structures of iRBCs caused by invasion of malaria parasites were represented by morphological alterations of RBCs . Hb concentration in RBC cytoplasm decreases because Hb is digested by malaria parasites and is converted into hemozoin as a byproduct.…”
Section: Resultsmentioning
confidence: 99%
“…It was confirmed that china 30 potency in monotherapy was capable of complete clearance of parasite with survival of mice up to 1 month follow up period. In earlier studies, monotherapy of china / was also reported to have statistically extremely significant effect on the reduction of P. berghei infection in BALB/c mice (Rajan and Bagai 2011). China is also recommended in homeopathic medical repertories against recurring, relapsing and intermittent type of malaria (Robert et al 2001;Kent 1989).…”
Section: Discussionmentioning
confidence: 99%
“…The drug completely cleared the infection when it was given in combination with standard antimalarial artesunate (100 mg/Kg). Both the monotherapy and combination were reported to be safe on the host's blood cells (Rajan and Bagai 2011). The homeopathic medicines can recondition entire human body through life force and by stimulating the natural defense mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…30 C) to combat rodent malaria parasite in P. berghei. This treatment cleared the parasite from circulation and increased survival rate (26.8 ± 1.2 days) of mice [1]. Chin.…”
Section: Introductionmentioning
confidence: 94%